THE PHENOMENON OF GLASS CEILINGS AND GENDER ISSUES IN WOMEN - Blangi Intan Maharani; Dwianita Dwianita (Journal Analytica Islamica, 2025)
As time goes by, women play a crucial role in improving the quality of both the public and domestic sectors. Negative perceptions that consistently emphasize women's presence in the workforce present a significant obstacle. One gender-related issue women face in advancing their careers is the glass ceiling. This study used a literature review method to further explore the glass ceiling and other gender-related issues that can impact women's careers. The results of this literature review indicate that while many women have overcome these barriers, the glass ceiling remains a crucial barrier to women's career advancement. Furthermore, this phenomenon contributes to social inequality, poor performance, and injustice for women within organizations.